2013
DOI: 10.1111/cyt.12105
|View full text |Cite
|
Sign up to set email alerts
|

Utility and pattern of positivity of p40 in the diagnosis of squamous cell carcinoma of the lung by cytology: the first study on fine needle aspiration smears

Abstract: p40 immunostain is a valuable stain in identifying lung SCCs and works well in aspiration smears. The pattern of positivity varies with the differentiation of the tumour and is seen prominently in higher grade SCC where in practice the need arises for distinguishing them from either poorly differentiated adenocarcinomas or non-small cell carcinoma, not otherwise specified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Cytology specimens are of paramount importance, not only in the diagnosis of tumors but for performing ancillary studies successfully [10][11][12] . Several recent publications regarding the use of cytological specimens in molecular testing of lung cancer have been published [3, 5-7, 13, 14] .…”
Section: Discussionmentioning
confidence: 99%
“…Cytology specimens are of paramount importance, not only in the diagnosis of tumors but for performing ancillary studies successfully [10][11][12] . Several recent publications regarding the use of cytological specimens in molecular testing of lung cancer have been published [3, 5-7, 13, 14] .…”
Section: Discussionmentioning
confidence: 99%
“…p40 expression has been reported to be specific for squamous cell carcinoma of the head and neck, esophagus, thymomas, urothelial carcinomas and lung squamous cell carcinoma [53,55,56,57,58]. Immunocytochemistry for p40 has been applied to cytology samples, such as cell blocks and fine-needle aspirates [59,60,61], with Collins et al [49] describing p40 as having 89% sensitivity and 100% specificity for non-small cell lung carcinoma. In our study, the sensitivity and specificity for p40 in squamous cell carcinoma were 84 and 98%, respectively (table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Although the World Health Organisation does recommend pattern subtyping on small biopsies and cytology samples whenever possible, its utility is controversial due to the sampling bias that will likely lead to incorrect classification. Nevertheless, subtyping of non‐small cell lung carcinomas (NSCLC) into ADs and squamous cell carcinomas has been found to be accurate and definite on cytology and small biopsy specimens . Among ADs alone, one previous study showed that cytological features correlate with prognosis, while others found that pattern grading on small biopsies predicts response to chemotherapy .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, subtyping of non-small cell lung carcinomas (NSCLC) into ADs and squamous cell carcinomas has been found to be accurate and definite on cytology and small biopsy specimens. 7,8 Among ADs alone, one previous study showed that cytological features correlate with prognosis, 9 while others found that pattern grading on small biopsies predicts response to chemotherapy. [10][11][12][13] In addition, knowledge of the varied patterns of lung ADs and its recognition will aid in triage of material for molecular analysis.…”
mentioning
confidence: 99%